How does arch form and interproximal contact size affect the 3D displacements and rotations of teeth: a finite element analysis - Andrea ÁLVAREZ; Santiago Alberto CORREA; Peter H. BUSCHANG; Samuel I. ROLDÁN (Dental Press Editora, 2024)
ABSTRACT Objective: The objective of this study was to determine how arch form and interproximal contact size displace mandibular teeth subjected to an anterior component of force (ACF). Methods: Nine finite element models (FEM) of the mandibular arch were developed using Ansys® v. 16.0 software. They were designed to evaluate the effects of three arch forms (triangular, oval, and square) and three contact sizes (point-to-point, 1 mm diameter, and 2 mm diameter). All nine models were subjected to an ACF of 53.8 N (5486 gm). Three-dimensional tooth rotations and displacements of the mandibular teeth were evaluated, from the right first molar to the left first molar. Results: Arch form had a greater effect on tooth movements than contact size. Triangular arches and point-to-point contacts produced the greatest displacements and rotations of teeth. Oval arches with 2 mm wide interproximal contact points showed the greatest stability. The right first premolar showed the greatest displacements in all of the models. Conclusions: Arch form and contact size affect interproximal tooth stability. Teeth are least stable in narrow arches with point-to-point interproximal contacts, and most stable in wider arches with larger contacts.